AFRICANAS Y AFROPEAS: VOCES FEMENINAS EN CRÉPUSCULE DU TOURMENT 1 MELANCHOLY DE LÉONORA MIANO. - Cuasante Fernández, Elena (Estudios Románicos, 2023)
Léonora Miano published in 2016 her novel Crépuscule du tourment 1 Melancholy. It is a choral work built upon a succession of 4 monologues in which four women recall their vital experiences. During this process, both Africans and Afropeans explore those pieces from the past that help us construct their current situation as women in the African continent. Crépuscule du tourment 1 Melancholy not only sheds light on some contemporary topics on African liteerature, but also elucidates upon the main ideas Leonara Miano brings forth in her last essays about very pressing matters such as frontier identities, African feminism and the reformulation of African-European relationship.